Nitrogen and Phosphorus in Coastal Systems: Focus on Dissolved Organic N and P - Padayao, Daisy; San Diego-McGlone, Maria Lourdes (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
Quantification of dissolved organic phosphorus (DOP) and dissolved organic nitrogen (DON) levels, and the relative importance of the organic fraction at various habitats (river, seagrass bed, mangrove area, coral reef, fishpen, and ocean) were the focus of this study. DON concentrations ranged from 9.5 to 44.3 µM during the dry season and from 10.9 to 23.7 µM during the wet season. DOP values ranged from 0.3 to 0.4 µM during the dry season and from 1.0 to 1.6 µM during the wet season. DON was 70-90% of the dissolved fraction in the first five habitats for both dry and wet seasons. DOP was approximately 15-35% during the dry season and 50-60% during the wet season. DON was highest in the river and lowest in the coral reef area for both seasons. High DOP concentrations were determined in the river and mangrove area in the dry season while lowest values were seen in the coral reef area. During the wet season, DOP was highest in the coral reef area and lowest in the mangrove area. When compared with oceanic systems, dissolved inorganic nitrogen (DIN) and dissolved inorganic phosphorus (DIP) have higher percentages (25-58% for DIN and 71-83% for DIP) in the open ocean than in coastal areas (10-32% for DIN and 62-67% for DIP). However, DON and DOP were the dominant forms in the coastal sites (42-75% DON vs 7-32% DIN and 17-30% DOP vs 35-67% DIP). The smaller fraction of the organic forms of N and P in the open ocean may be indicative of the greater efficiency in nutrient recycling/regeneration in the open ocean than in the coastal area. N:P ratios in the five habitats ranged from 2 to14 with the highest ratio in the coral reef area.
Keywords: dissolved organic nitrogen (DON); dissolved organic phosphorus (DOP); dissolved inorganic nitrogen (DIN); dissolved inorganic phosphorus (DIP); coastal habitats